Analysis of Perceptions and Knowledge in Managing Coastal Resources: A Case Study in Fiji - Kitolelei, Jokim V.; Sato, Tetsu (Frontiers in Marine Science, 2016)
Sustainable management of coastal resources depends on human knowledge and perceptions of natural resources and coastal environments. However, empirical evidence has been limited in order to understand linkages between knowledge, perceptions and collective actions to achieve sustainable resource management. This case study analyzed perceptions and knowledge among diverse stakeholders: villagers, government officials, scientists and staff of a non-governmental organization who are collaboratively working in a Fijian coastal community to manage the local coastal resources. Analyses were made using the integrated local environmental knowledge (ILEK) concept and frameworks of discourse analysis to clarify interlinkages between perceptions, knowledge and collective actions for a variety of examples. Research was conducted in Kumi village on the island of Viti Levu in Fiji, and the investigated projects included the management of a locally managed marine area, seaweed aquaculture, sea cucumber restoration and ginger plantations. These initiatives have shown that diverse knowledge on coastal resources and environments influence perceptions among people in a complex way, and transformation of perceptions produced new sets of knowledge through the generation of hypotheses regarding the management of coastal resources. Collective actions were promoted by the transformation of perceptions, and social learning processes were mobilized by these collective actions. Traditional institutions, cultures and leadership roles deeply embedded in the local communities had strong influences on shared perceptions among community members to provide foundations for collective actions. Dynamic transformations of perceptions promoted by integrated knowledge among community members were critical enablers of collective actions to achieve sustainable resource management.